Evaluation of Government Policies in Infrastructure Development: Effectiveness, Challenges, and Community Impact - Lalo, Malomo (IHSA Institute, 2025)
Infrastructure development is a key driver of economic growth, social progress, and improved quality of life. Effective government policies play a crucial role in ensuring that infrastructure projects are well-planned, efficiently executed, and sustainable. This research evaluates government policy effectiveness in infrastructure development by analyzing policy frameworks, financing mechanisms, governance structures, and technological advancements. The study also assesses public perception and the social, economic, and environmental impacts of infrastructure projects on communities. By comparing infrastructure policies with global best practices, the research highlights the importance of strategic planning, public-private partnerships (PPPs), digital transformation, and sustainable development principles. Findings suggest that countries with transparent governance, long-term investment strategies, and strong community engagement achieve more successful infrastructure outcomes. Conversely, challenges such as corruption, inadequate funding, and lack of public participation often hinder policy effectiveness. The study concludes that governments must enhance policy effectiveness by adopting adaptive policymaking, innovative financing, and inclusive planning approaches to maximize infrastructure benefits. Future research should explore technological innovations and policy reforms that can further optimize infrastructure development for long-term economic and social resilience.